Sodium benzoylpaeoniflorinsulfonat và sodium paeoniflorinsulfonat, hai hợp chất mới được phân lập từ rễ cây bạch thược (Paeonia lactiflora). - Yến, Phạm Hải; Minh, Châu Văn; Kiệm, Phan Văn; Nhiệm, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
From the roots of Paeonia lactiflora Pall. two new compounds as sodium benzoylpaeoniflorinsulfonate (1) and sodium paeoniflorinsulfonate (2) were isolated by various chromatography methods. Their chemical structures were elucidated by ESI-MS, HR-ESI-MS and 1D, 2D NMR experiments and by comparison of their NMR and ESI-MS data with previous reported data.